2023
DOI: 10.3390/min13020181
|View full text |Cite
|
Sign up to set email alerts
|

Applied Methodological Approach for the Assessment of Soil Contamination by Trace Elements around Abandoned Coal Mines—A Case Study of the Jerada Coal Mine, Morocco

Abstract: Previously conducted studies have established that soil contamination by trace elements (TEs) around coal mines affects ecological biodiversity and human health. One of the ways to protect the health of the surrounding population of coal mine sites is through the assessment of contamination impacts by accurate procedures for the establishment of relevant reclamation plan. The aim of the study is to develop an applied methodological approach to easily assess and quantify the impact of coal mining on the surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Environmental problems are most often caused by facilities built in the previous century, at a time when less attention was paid to environmental issues. Numerous studies from around the world have shown the negative impact of mining waste on the environment through the distribution of microelements in soil and groundwater [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental problems are most often caused by facilities built in the previous century, at a time when less attention was paid to environmental issues. Numerous studies from around the world have shown the negative impact of mining waste on the environment through the distribution of microelements in soil and groundwater [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment factor is used to assess the degree of anthropogenic influence on ecosystems. The results determine five classes: deficiency to minimal enrichment (<2), moderate enrichment (2-5), significant enrichment (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), very high enrichment , and extremely high enrichment (>40). • Translocation factor (TF): TF = C n R n , where C n is the element content in the aboveground parts of the plant, and B n is the concentration of the same element in the roots [58,59].…”
mentioning
confidence: 99%
“…The amount of overburden is increasing. Various researchers are attempting to solve this problem using these breeds in the economy [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It must be underlined that methods of soil/tailing stabilization are subject to current development and valuable contributions concerning both sources of contamination and protective measures are being published worldwide [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%